New Afrotropical species of the bee subgenus Patellapis (Chaetalictus) with notes on additional species (Hymenoptera: Halictidae) - Kuhlmann, Michael; Pauly, Alain (Zootaxa, 2010)
For the African bee subgenus Patellapis (Chaetalictus) five species are here described as new: P. (Ch.) itigiensis sp. n., P. (Ch.) kahuziensis sp. n., P. (Ch.) knersvlaktei sp. n., P. (Ch.) rutshuruensis sp. n., and P. (Ch.) upembae sp. n. The recently discovered female of P. (Ch.) namaquensis Timmermann 2009 is described here for the first time and the nomenclatural status of P. (Ch.) pulchrinitens (Cockerell 1942) is corrected to P. (Ch.) pulchrilucens (Cockerell 1943).